Synergy - Mizusaki, Jorge Mitsuo (Scientific Journal of the Foot & Ankle, 2018)
This number represents the third publication of volume 12 of the official publication of the Brazilian Association of Medicine and Surgery of the Foot and Ankle. Is already released for on-line consultation (anticipated), to the extent that the volume of articles makes possible the optimization of our services. This brings benefits to authors and readers but increases the need to observe the guidelines that govern the formatting and execution of the scientific articles. It is an activity that counts with the collaboration of individuals trained to observe and apply the rigor of the technical standards of scientific publication. What is certain is that we must remain vigilant and accustomed ourselves with the specifics of the scientific production, and the planning of the methods of data collection and the subsequent analysis of them. The submission of this protocol to the analysis of the ethics committees in research is what will give the endorsement so that it can execute it and, at the end, publish it. It becomes necessary that we are used to the rigor of the required procedures. In this sense, it is important that the sources of research funding are properly pointed out and that the results are adequately informed. The motivation to publish is directly associated with the desire to provide a high contribution to the technical-scientific knowledge on the surgery of the foot and ankle. We should also highlight the need to extend the training centers of orthopedists trainers’ and specialized in surgery of the foot and ankle, therefore, ensure the quality of our publications, based on rigid ethical, technical and scientific training. This edition brings a variety of articles that provides the surgeon of the foot and ankle a broad overview of the potential of our specialty, showing the regional differences and indicating what is open to all who are interested in study, teach, and reach a higher step in the actions for the well-being of our society. The members of our ABTPé have already demonstrated the ability to promote events that are of great importance for the diffusion of knowledge. The moment requires synergistic action to achieve the ideals pursued. Have all a great read. Jorge Mitsuo Mizusaki Editor-in-Chief